2015
DOI: 10.1007/s12310-014-9140-x
|View full text |Cite
|
Sign up to set email alerts
|

School- and Classroom-Based Supports for Children Following the 2013 Boston Marathon Attack and Manhunt

Abstract: School staff provide key mental health services following mass crisis events and teachers, in particular, can provide important supports within their classrooms. This study examines Boston-area teachers’ perception of classroom-wide psychiatric distress and the types of supports that schools and teachers provided following the 2013 Boston Marathon bombing and subsequent manhunt. Boston-area K-12 teachers (N = 147) in communities with varying levels of exposure to the bombing and manhunt completed an anonymous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
(33 reference statements)
0
9
2
Order By: Relevance
“…Although previous work documents the mental health toll of the Boston Marathon bombing and its aftermath on many Boston-area children, [10,11] the present findings indicate that children with close relatives in law enforcement or the armed forces who participated in the unprecedented interagency manhunt carried a particularly heavy mental health burden. Although it has been estimated that only 0.4-1.5% of the general child population has severely impairing PTSD, [37,38] roughly one out of every nine children sampled with family in the manhunt had "likely PTSD."…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Although previous work documents the mental health toll of the Boston Marathon bombing and its aftermath on many Boston-area children, [10,11] the present findings indicate that children with close relatives in law enforcement or the armed forces who participated in the unprecedented interagency manhunt carried a particularly heavy mental health burden. Although it has been estimated that only 0.4-1.5% of the general child population has severely impairing PTSD, [37,38] roughly one out of every nine children sampled with family in the manhunt had "likely PTSD."…”
Section: Discussioncontrasting
confidence: 87%
“…Although research has highlighted the toll of the Marathon bombing on Boston‐area youth, exposures to the subsequent manhunt have actually been more robustly associated than attack‐related exposures with a range of psychosocial outcomes . While such work clarifies the broad impact of manhunt‐related experiences on Boston‐area youth, it does little to inform our understanding of the specific clinical needs of a particularly vulnerable population: children with a relative in law enforcement or the armed services deployed in the manhunt.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These interventions are often efforts from professionals external to the school system. However, there are a growing number of studies on creating trauma-informed schools with focus on school service delivery and a more comprehensive integration of trauma-informed approaches into the larger school context (Fu & Underwood, 2015 ; Green et al, 2015 ; Overstreet & Chafouleas, 2016 ). The Utøya survivors were mostly students in upper secondary school or higher education programs.…”
mentioning
confidence: 99%
“…Similarly, studies of K-12 teachers following trauma have found that teachers vary greatly in their knowledge of student crisis-related needs and provision of classroombased supports (Felix et al, 2010;Green et al, 2015). These studies suggest that providing training for faculty and instructors on student MH, in general, and guidelines around how to respond to trauma, specifically, might be particularly beneficial to students.…”
Section: University Response Post-tragedymentioning
confidence: 99%